2016
DOI: 10.1007/s10266-016-0273-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Er,Cr:YSGG laser irradiation on bovine enamel surface during in-office tooth bleaching ex vivo

Abstract: The aim of this in vitro study was to evaluate the effect of using Er,Cr:YSGG laser during in-office tooth bleaching on bovine enamel surface to evaluate the safety of this therapy on tooth tissues. Thirty-six enamel specimens were prepared from bovine incisors and divided into three groups: Group 1 specimens (control) received no bleaching treatment; Group 2 received a conventional in-office bleaching treatment (40 % HO); Group 3 received laser-assisted bleaching procedure (40 % HO) utilizing an Er,Cr:YSGG la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 30 publications
2
20
0
Order By: Relevance
“…Therefore, it might be said that preference of Er,Cr:YSGG laser in bleaching agents activation seems safer than the diode laser. In line with our study, Dionysopoulos et al 39 asserted that Er;Cr:YSGG laser‐activated bleaching process does not considerably change enamel mineral content or surface morphology compared to the conventional chemical whitening procedure.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, it might be said that preference of Er,Cr:YSGG laser in bleaching agents activation seems safer than the diode laser. In line with our study, Dionysopoulos et al 39 asserted that Er;Cr:YSGG laser‐activated bleaching process does not considerably change enamel mineral content or surface morphology compared to the conventional chemical whitening procedure.…”
Section: Discussionsupporting
confidence: 92%
“…The composition of artificial saliva was as follows: 0.103 g/l of CaCl 2 , 0.019 g/l MgCl 2 ·6H 2 O, 0.544 g/l KH 2 PO 4 , and 2.24 g/l KCl, and buffer (TCP-KOH) was added to adjust the pH to 7. [ 9 ]…”
Section: Methodsmentioning
confidence: 99%
“…The distinction in results may be attributed to the difference of light source used in the bleaching procedure (70) . Dionysopoulos et al, (2017) found that a slight reduction in enamel surface micro-hardness and changes in surface morphology may occur when high-concentrated bleaching agents were used for power in-office tooth bleaching and there was acceleration in bleaching process. Dissimilarity in results may be attributed to difference in source of activation, where in the current study LED was used whereas Er,Cr:YSGG laser was used in the other study which advised the use of Er,Cr:YSGG laser in-office tooth bleaching safely (71) .…”
Section: Discussionmentioning
confidence: 99%